Protection on Indonesian Migrant Workers Under The Indonesia-Japan Economic Partnership Agreement (IJEPA) - Naeli, Fitria (Westscience Press, 2025)
Growing numbers of Indonesian migrant workers in Japan have become an intrinsic part of Indonesia-Japan bilateral cooperation, particularly through the Indonesia-Japan Economic Partnership Agreement (IJEPA). This essay examines the extent to which the rights of Indonesian workers are secured in this cooperation based on liberalism theory in international relations. Liberalism focuses much on interdependence, mutual gains, and institutional cooperation, which is seen in the controlled labor agreements between the two nations. Programs such as the Technical Intern Training Program (TITP) and the Specified Skilled Worker (SSW) scheme have encouraged skills development and economic growth for Indonesian workers in addition to alleviating Japan's labor shortages. Challenges exist, however, with issues of language, cultural adaptation, and workplace exploitation despite such controlled systems. Through response to these challenges, Indonesia and Japan have devised multi-layered associations with administrative units, business corporations, and Non-Government Organizations. Welfare services of employees fall under the ambit of organizations like the Japan International Corporation of Welfare Services (JICWELS) and the Association of Overseas Apprentices (AP2LN), whereas diplomatic interventions, such as performed by the Indonesian Consulate General of Osaka, complement preventive strategies. IJEPA is a legal framework for such collaboration, encouraging labor migration policies that respect the dignity and fair treatment of workers. This study underlines the necessity of continuous dialogue and policy enhancement to enhance the protection and economic contribution of Indonesian migrant workers in Japan. Strengthening cooperation in the liberal framework can also ensure that labor migration is a win-win element of Indonesia-Japan relations. Keywords: Indonesia-Japan cooperation, Indonesian migrant workers, Liberalism theory, IJEPA, worker protection